Determinants for sustainability in the dairy industry in Malaysia - Nguang, S. I; Nalini, A.; Abdul Rashid, B. (2014)
Malaysian dairy sectors considered as small with the level of milk sufficiency about 9% but the government aims are to double local milk production in the short term as well as the long term and to increase self-sufficiency level to higher level. Most of the dairy farmers in Malaysia consist of smallholders. In order to improve the dairy industry in Malaysia, it is important for dairy farmers adapting the sustainability practices in their management and farm operation. Implementation of sustainable practices in dairy should starts from the farm where the farmers should understand the concept thoroughly as they can do the practices effectively in the long run. Sustainable practices also will lead to increase in profits, enhance food security as well as sustaining the ecological and social aspects. This study attempts to investigate the determinants in sustainability as well as describing the socio economic characteristics and information seeking behaviour of the dairy farmers which will be the guidelines to develop recommendation to accelerate adoption of sustainability among dairy farmers. The preliminary data was collected using questionnaires through conducting face to face interviews with 50 dairy farmers from Johor. The likert-like scale was employed to determine the practices that adopted by the dairy farmers. The gathered data was analysed using SPSS. The findings indicated that the dairy farmers had a higher understanding about the farm sustainability aspect which gives the highest mean score of 4.41. The second highest mean score is the ecological aspect which is about 4.13. The mean score for economic aspect shows the mean score about 4.00. The social aspect of sustainability revealed the lowest mean score which was about 3.46. The results indicated that the most favourable sustainable practice is farm sustainability. The dairy farmers should have in depth knowledge in farm sustainability, economic sustainability, social sustainability and ecological sustainability to enhance the dairy farming industry.